2015
DOI: 10.1007/s13314-015-0181-2
|View full text |Cite
|
Sign up to set email alerts
|

Association of 16SrII-C and 16SrII-D subgroup phytoplasma strains with witches’ broom disease of Parthenium hysterophorus and insect vector Orosius albicinctus in India

Abstract: Parthenium weed (Parthenium hysterophorus, Asteraceae) is a common, invasive weed found throughout the Indian subcontinent, Africa, America and Australia. The observed disease, Parthenium Witches' Broom (PWB), characterised by phylloidy, stunting and prolific branching was observed during a field survey conducted between September 2014 to June 2015. PWB phytoplasma was detected in all symptomatic plant samples and in the previously reported insect vector, Orosius albicinctus belonging to family Cicadellidae (s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 15 publications
1
10
0
Order By: Relevance
“…Orosius albicinctus resulted the vector of the disease in Bandar Abbas confirming its vector ability reported for diverse phytoplasmas to different plant species (Esmailzadeh‐Hosseini, Mirzaie, Jafari‐Nodooshan, & Rahimian, ; Ikten et al, ; Nikooei & Hemmati, ; Omidi, Hosseini Pour, Massumi, & Rahimian, ; Salehi et al, ; Yadav, Thorat, Bhale, & Shouche, ). For instance, Vasudeva and Sahambi () reported that Orosius spp.…”
Section: Discussionsupporting
confidence: 61%
“…Orosius albicinctus resulted the vector of the disease in Bandar Abbas confirming its vector ability reported for diverse phytoplasmas to different plant species (Esmailzadeh‐Hosseini, Mirzaie, Jafari‐Nodooshan, & Rahimian, ; Ikten et al, ; Nikooei & Hemmati, ; Omidi, Hosseini Pour, Massumi, & Rahimian, ; Salehi et al, ; Yadav, Thorat, Bhale, & Shouche, ). For instance, Vasudeva and Sahambi () reported that Orosius spp.…”
Section: Discussionsupporting
confidence: 61%
“…The parthenium plants infected with phytoplasma in the vicinity of an alfalfa field had identical symptoms such as short proliferation with short internodal followed by floral deformation (Fig 2C). Yadav et al (2015) reported the phytoplasma infecting Parthenium hysterophorus shares 99.3% rDNA sequence similarity with 'Ca. P. aurantifolia' 16S rDNA II-D.…”
Section: Disease Symptoms and Incidencementioning
confidence: 99%
“…Majority of these genes associated with either host plant resistance mechanisms against various pathogens and pests or the biotic stresses. Thus, the P. hysterophorus plants might have showed greater endurance to biotic and abiotic stresses, and showed its best survival nature baring a few such as witches broom disease (Li et al 2011;Keshwal, 1982;Yadav et al 2015;Fauzi, 2009). Further, the expression pattern of some of the pathogenesis related genes viz; pathogenesis-related protein 1 (PR-1), nematode resistance protein-(HSPRO2), rust resistance kinase Lr10, chitinase1, leaf rust 10 disease-resistance locus receptor-like protein kinase (Like 1.3), and defensin-A3 were evaluated among different tissue of healthy plant as well as phytoplasma infected plants (Table 4; Figure 3) showing symptoms of witches broom disease.…”
Section: Functional Annotation Of Orthologous Genes Clustersmentioning
confidence: 99%
“…In nature, it's very hard to detect any organism which are parasitizing on P. hysterophorus. Very rarely some fungus like rust causing and witches broom disease caused by phytoplasma are reported (Li et al 2011;Keshwal, 1982;Yadav et al 2015). Further, expression of some pathogenesis related genes like (TMV) disease resistance protein RPP4, pathogenesis-related protein PR-1, and leaf rust 10 disease-resistance locus receptor in phytoplasma infected plants were found to be suppressed.…”
Section: Cr Cu Fementioning
confidence: 99%